A Study of the Determinants of Corporate Environmental Disclosure in MENA Emerging Markets - Akrout, Mejda Mahmoudi; Othman, Hakim Ben (Journal of Reviews on Global Economics, 2013)
Abstract: The purpose of this study is to investigate environmental disclosure determinants in Arab Middle Eastern and North African (MENA) companies. In this regard, we investigate factors which are specific to this context. We include the â€˜business culture’ variable inherited from former colonisers and main economic partners and the â€˜state ownership’ and â€˜family ownership’ variables. In addition, we consider â€œCountry’s Internet Penetrationâ€ as a new explanatory variable which is expected to influence environmental disclosure on the web site. Using a sample of 153 web sites of listed companies, findings show a negative and significant relationship between environmental disclosure and â€˜family ownership’. Moreover, consistent with prior work, the level of environmental disclosure is substantially affected by company size and performance.